catalyst

CN111051358BActive Publication Date: 2026-10-16BOREALIS AG
View PDF 24 Cites 0 Cited by

Patent Information

Application Number
CN201880055927.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-10-24
Filing Date
2018-10-23
Publication Date
2026-10-16
Estimated Expiration
2038-10-23

AI Technical Summary

Technical Problem

此外,由于复制效应,催化剂的窄粒度分布将导致聚合物的窄粒度分布

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002393893410000211
    Figure BDA0002393893410000211
Patent Text Reader

Abstract

The present invention relates to a Ziegler-Natta catalyst component in the form of solid particles having a median particle size (D50 vol ) of 5 to 200 µm and comprising i) a compound of a Group 1 to 3, preferably Group 2 metal according to IUPAC Inorganic Chemistry Nomenclature 1989, ii) a compound of a transition metal of Group 4 to 10 or of the lanthanide or actinide series, preferably of Group 4 to 6, according to IUPAC Inorganic Chemistry Nomenclature 1989, and iii) an internal electron donor, wherein the number SPAN of the solid particles is 0.80 or less and the ratio of number mode to volume mode (mode num / mode vol ) is 0.60 or more, and wherein the mode num < mode vol . The present invention further relates to a process for producing said catalyst component and its use for producing C2 to C 10 α-olefin polymers, in particular propylene or ethylene polymers or copolymers thereof with α-olefins of 2 to 12 C atoms.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to solid Ziegler-Natta catalyst components for the production of olefin polymers and their preparation. Furthermore, this invention relates to Ziegler-Natta catalysts comprising said solid catalyst components, a Group 13 metal compound as a co-catalyst, and optionally an external electron donor. The invention also relates to said catalyst components in the production of C2 to C4 polymers. 10 Uses of olefin polymers and their (co)polymers with other olefins having 2 to 12 C atoms, especially ethylene and propylene polymers and their copolymers. Background of the Invention

[0003] Ziegler-Natta (ZN) type polyolefin catalysts are used in the production of olefin polymers, such as C2 to C3. 10 The field of olefin polymers and their (co)polymers with other α-olefins having 3 to 12 carbon atoms is well known. Typically, catalysts comprise at least a catalyst component (formed from transition metal compounds of Groups 4 to 10 of the Periodic Table (IUPAC, Inorganic Chemical Nomenclature, 1989) or lanthanides or actinides), compounds of metals of Groups 1 to 3 of the Periodic Table (IUPAC), and optionally compounds of Group 13 of the Periodic Table (IUPAC), and optionally an internal organic compound such as an internal electron donor. ZN catalysts may also comprise other catalyst components, such as a co-catalyst and optionally an external electron donor.

[0004] A wide variety of Ziegler-Natta catalysts have been developed to meet different requirements in terms of reaction characteristics and for the production of poly(α-olefin) resins with desired physical and mechanical properties. Typical Ziegler-Natta catalysts contain magnesium compounds, titanium compounds, and optionally aluminum compounds supported on particulate supports. Commonly used particulate supports are based on Mg dihalides, preferably MgCl2-based supports, or inorganic oxide supports such as silica, alumina, titanium dioxide, silica-alumina, or silica-titanium dioxide, typically silica.

[0005] Typical MgCl2-based Ziegler-Natta catalysts contain titanium compounds and optional Group 13 compounds, such as aluminum compounds. Such catalysts are disclosed, for example, in EP376936, EP591224, WO 2005 / 118655 and EP 810235, which also disclose spray drying or spray crystallization methods for producing MgCl2-based support materials.

[0006] The catalyst components can be prepared by sequentially contacting an inorganic support with the aforementioned compounds, for example, as described in EP688794 and WO 99 / 51646. Alternatively, it can be prepared by first preparing a solution from each component and then contacting the solution with the support, as described in WO 01 / 55230.

[0007] Another method for producing solid Zn catalyst components is based on a process in which the catalyst component is reacted in solution, and the solid catalyst component is obtained by curing or precipitation. Such preparation methods are described, for example, in patent publications WO2003 / 000757, WO2003 / 000754, WO2004 / 029112, WO2007 / 137849, WO2007 / 137853, WO2012 / 007430, WO2013 / 098149, WO2013 / 098137, and WO2013098138.

[0008] The aforementioned ZN catalyst is claimed to be used for olefin polymerization, for example for the production of polymers of α-olefins with 2 to 6 carbon atoms, especially ethylene, propylene, 1-butene, or their (co)polymers with ethylene and / or other α-olefins with 3 to 12 carbon atoms.

[0009] However, even though many existing catalysts have shown satisfactory performance for many applications, there is still a need to modify and improve the performance of catalysts in order to obtain the desired performance in the desired polymerization process and to obtain the desired polymer properties.

[0010] Catalyst particle size and particle size distribution are important in polymerization processes, and a reasonably uniform particle size distribution is generally desired. The particle morphology of supported catalysts is highly dependent on the morphology of the support material. Solid catalyst components or catalyst support materials can be classified according to particle size and particle size distribution using conventional sorting techniques, such as sieving. Although much development work has been done in Ziegler-Natta catalyst preparation, there is still room for improvement, especially in terms of particle size and particle size distribution characteristics. Typically, it is necessary to sort particles according to catalyst particle size to obtain catalysts in the form of solid particles with the desired uniform particle size, i.e., the desired narrow particle size distribution. However, any sorting step implies an additional step in catalyst preparation. A common method for screening particles is sieving. Fines can also be removed, for example, along with liquids (e.g., washings). However, this not only removes unwanted catalyst particles but also results in additional work and cost. In addition, removing a portion of catalyst particles from the produced material reduces the overall yield of the produced catalyst. The removed portion of the catalyst, i.e., the unwanted particles, forms waste material, which is disposed of according to strict environmental requirements and regulations. If catalyst debris is not removed, it can easily cause problems in later use, such as clogging of reactors, pumps, and process lines. Therefore, even though catalyst components with a reasonably narrow particle size distribution (PSD) are disclosed in patent literature in the form of solid granular materials, there remains room for providing catalysts with even narrower PSDs. In particular, it would be highly desirable to provide granular catalysts with reduced amounts of extremely small particles, without requiring any screening steps after catalyst formation to remove unwanted catalyst fractions, especially extremely small catalyst particles. Furthermore, it should be noted that catalyst yields in catalyst production will be higher when no removal step is required.

[0011] Due to the replication effect, polymer particles will follow the morphology of catalyst particles; that is, a catalyst with a narrow particle size distribution should produce a polymer with a similar narrow particle size distribution. However, the resulting polymer will naturally have a larger particle size. It is highly desirable to reduce the formation of debris during polymerization, as debris causes several problems in the process and the final polymer. Debris formation can cause serious problems, especially in process configurations that include one or more gas-phase reactors. Such approaches can be single-stage or multi-stage, including at least one gas-phase reactor and optionally at least one slurry polymerization reactor. Therefore, preventing debris formation in continuous full-scale polymerization is crucial to prevent reactor contamination and to ensure smooth operation of multiple polymerization processes without any unplanned process downtime. This phenomenon is not observed in small-scale laboratory or laboratory-scale batch processes, but it is a practical problem in continuous large-scale polymerization processes, especially in process configurations that include at least one gas-phase reactor.

[0012] Using catalysts with more uniform particle size (i.e., a narrow particle size distribution) and significantly smaller particles in a reduced quantity within the solid catalyst material can effectively reduce or completely eliminate the formation of fine particles during polymerization. Therefore, problems such as clogging caused by catalyst fine particles can be avoided or at least substantially reduced. Furthermore, due to the replication effect, the narrow particle size distribution of the catalyst will result in a narrow particle size distribution of the polymer. As a further benefit, polymers with a narrow particle size distribution are easier to handle in post-reactor processes. Invention Overview

[0014] It has now been surprisingly found that when using a SPAN of 0.80 or lower during polymerization and a ratio of quantity mode to volume mode (mode) num / model vol When the solid Ziegler-Natta catalyst is 0.60 or higher, many problems in polymerization methods stemming from unsatisfactory catalyst particle size and particle size distribution can be solved. Furthermore, it has now been found that such catalyst particles can be obtained directly from the catalyst manufacturing process without the need for any catalyst sorting method based on catalyst particle size to remove unwanted catalyst particles, especially those that are too small, such as catalyst chips.

[0015] Therefore, the object of the present invention is to provide a Ziegler-Natta catalyst component having a median particle size (D50). vol It is in the form of solid particles ranging from 5 to 200 μm and contains:

[0016] i) Compounds of Groups 1 to 3, preferably Group 2 metals, according to the IUPAC Inorganic Chemical Nomenclature of 1989.

[0017] ii) Compounds of transition metals of groups 4 to 10, or lanthanides or actinides, preferably transition metals of groups 4 to 6, as per the IUPAC Inorganic Chemical Nomenclature of 1989, and

[0018] iii) Internal electron donor,

[0019] The number of solid particles, SPAN, is 0.80 or lower, and the ratio of the number pattern to the volume pattern (pattern) is... num / model vol The value is 0.60 or higher.

[0020] Furthermore, an object of the present invention is to provide a method for producing olefin polymers in the presence of a Ziegler-Natta catalyst component, wherein the Ziegler-Natta catalyst component has a median particle size (D50). vol It is in the form of solid particles ranging from 5 to 200 μm and contains:

[0021] i) Compounds of Groups 1 to 3, preferably Group 2 metals, according to the IUPAC Inorganic Chemical Nomenclature of 1989.

[0022] ii) Compounds of transition metals of groups 4 to 10, or lanthanides or actinides, preferably transition metals of groups 4 to 6, as per the IUPAC Inorganic Chemical Nomenclature of 1989, and

[0023] iii) Internal electron donor,

[0024] The number of solid particles, SPAN, is 0.80 or lower, and the ratio of the number pattern to the volume pattern (pattern) is... num / model vol The value is 0.60 or higher.

[0025] Furthermore, the object of the present invention is to provide a method for producing the Ziegler-Natta catalyst components as defined above.

[0026] Furthermore, the object of this invention is the use of the Ziegler-Natta catalyst component as defined above for the production of C2 to C3. 10 Olefin polymers and their C2 to C3 polymers 12 Applications of copolymers of olefin monomers.

[0027] In addition, the present invention relates to a catalyst comprising the Ziegler-Natta catalyst components as defined above, a co-catalyst, and optional external additives such as external electron donors, and the use of said catalyst in olefin polymerization methods.

[0028] In this disclosure, the term internal electron donor refers to a compound that is part of the solid catalyst component (i.e., added during its synthesis). External electron donor refers to a component that is not part of the solid catalyst component but is fed separately into the polymerization process. Invention Details

[0030] In this application, the following metrics are used for catalyst particle size and particle size distribution:

[0031] Particle size distribution (PSD):

[0032] A typical way to define PSD is to give SPAN as the relative distribution of particle-based volume quantities, i.e., as volume SPAN (SPAN vol ).

[0033] SPAN v o l =(D90) v o l –D10 v o l ) / D50v o l

[0034] in

[0035] D90 vol = The volume fraction of the particle diameter at 90% of the cumulative size, meaning 90% by volume of the particles are smaller than this diameter.

[0036] D10 vol = The volume fraction of the particle diameter at 10% of the cumulative size, i.e., 10% by volume of particles smaller than this diameter.

[0037] D50 vol = The volume percentage of particle diameter at 50% cumulative size, meaning 50% by volume of particles are smaller than this diameter and 50% by volume of particles are larger than this diameter. D50 vol It is the median particle size by volume.

[0038] SPAN vol D90 vol D10 vol and D50 vol In this field, it is common to use the term "without subscript " vol The following are disclosed under the condition that they are SPAN, D90, D10 and D50 respectively.

[0039] Another way to define a PSD is based on the number of SPANs (SPANs) num ).

[0040] The quantity SPAN is defined as follows:

[0041] SPAN num =(D90) num –D10 num ) / D50 num

[0042] in

[0043] D90 num = The number of particles at 90% cumulative size, i.e., 90% of the particles are smaller than this diameter.

[0044] D10 num = The number of particles at 10% cumulative size, i.e., 10% of the particles are smaller than this diameter.

[0045] D50 num = The number of particles at 50% cumulative size, i.e., 50% of the particles are smaller than this diameter and 50% of the particles are larger than this diameter.

[0046] As defined above, the median granularity D50 represents a granularity where half of the particles are above a given value and the other half are below that value.

[0047] -D50 vol It is the median granularity of the volume distribution, and

[0048] -D50 num It is the median granularity of the quantity distribution.

[0049] In this application, if no subscript is marked in SPAN, D90, D10, and D50, vol These refer to volume values, while quantities SPAN, D90, D10, and D50 are indicated by subscripts "". num "mark.

[0050] Volume SPAN and number SPAN values ​​provide different information about particle size distribution. By definition, volume SPAN is based on the volume of particles, while number SPAN is based on the number of particles.

[0051] model:

[0052] The pattern represents the most common grain size (or size range) in the grain size distribution, corresponding to the highest peak in the differential distribution. In this application, the pattern is defined by a volumetric pattern (pattern). vol ) and quantity patterns (patterns) num The mode is defined as a modal diameter.

[0053] Particle size measurements can be performed using instruments based on different methods. Measurements can be based, in particular, on determining the size of individual particles, i.e., using a single particle counter. Some instruments determine volume and size. A differential number-weighted distribution can be converted to a differential volume-weighted distribution by multiplying the number by the cube of the diameter. However, due to several uncertain error factors, it is not recommended to convert the measurement results of a volume-weighted particle size distribution to a number-weighted distribution. Therefore, such a conversion result is unreliable. The differential distribution shows the relative quantity (e.g., by number or volume) at each size. In this application, the measurement is based on a method using a single particle counter.

[0054] Volume distributions always shift towards larger particle sizes than number distributions; and the pattern of volume distributions is higher than that of number distributions for the same material. In counting experiments, even a few relatively large particles dominate the volume distribution, thus shifting the pattern. vol Move to a larger granularity, while increasing the number of patterns (patterns) num It is more sensitive to small particles, thus shifting the quantity distribution to smaller particles.

[0055] Furthermore, compared to number SPAN (which also considers all particles, i.e., the number of particles), the weighting of small particles in volume SPAN is smaller. Therefore, in the same material, D50 num It can and typically has more features than the D50. vol Lower values. Small SPAN vol and Little SPAN num The combination of these terms indicates that the granular material has a narrow particle size distribution.

[0056] Therefore, smaller patterns num A higher value indicates a higher quantity of small particles; conversely, a lower value indicates a higher mode. num The value indicates a lower quantity of small particles. Therefore, if smaller particles are undesirable, the quantity pattern should have a higher value. Ideally, the quantity pattern should approximate the volume pattern, but its value should always be lower than the volume pattern value.

[0057] Therefore, the relative positions of the volume and quantity pattern distribution peaks, i.e., the ratio pattern num / model vol This further indicates the presence of fine debris within the granular material. Therefore, it is associated with a smaller pattern. num / model vol Compared to materials with higher ratios, the pattern is more suitable. num / model vol The ratio indicates the presence of fewer fine particles.

[0058] Therefore, the quantity value D90 num D10num, D50 num SPAN num and pattern num Additional important information regarding the particle size and particle size distribution of granular materials is provided. Different granular materials with the same level of volume SPAN may still have different particle sizes (SPAN). num There are significant differences in this aspect. num The lower the value, the fewer small particles are present in the granular material.

[0059] catalyst components

[0060] As indicated above, the object of this invention is to provide median granularity (D50). vol The Ziegler-Natta catalyst component is a solid particle in the form of 5 to 200 μm particles, comprising:

[0061] i) Compounds of Groups 1 to 3, preferably Group 2 metals, according to the IUPAC Inorganic Chemical Nomenclature of 1989.

[0062] ii) Compounds of transition metals of groups 4 to 10, or lanthanides or actinides, preferably transition metals of groups 4 to 6, as per the IUPAC Inorganic Chemical Nomenclature of 1989, and

[0063] iii) Internal electron donor,

[0064] The number of solid particles mentioned above is SPAN (SPAN num The ratio of the number pattern to the volume pattern is 0.80 or lower (pattern). num / model vol The value is 0.60 or higher, and the mode is... num <mode vol .

[0065] Therefore, 0.60≤ pattern num / model vol It is <1.0.

[0066] The solid particles as defined above are obtained from a preparation process of any desired catalyst component without removing any unwanted catalyst particles. Therefore, the final catalyst component in solid particle form according to the invention is obtained without employing any screening steps.

[0067] Preferably, SPAN num The value is 0.70 or lower, more preferably 0.60 or lower, or even 0.50 or lower. Therefore, in a particularly preferred embodiment, SPAN... num It is at most 0.50.

[0068] The median particle size D50 of the catalyst component of the present invention vol Preferably, the D50 is in the range of 8 to 200 μm, more preferably in the range of 10 to 150 μm. In some embodiments, D50 vol Preferably in the range of 20 to 100 μm.

[0069] Ratio pattern of catalyst components in solid particle form num / model vol ≥0.60, preferably ≥0.70, more preferably 0.80 or higher, even 0.85 or higher, but less than 1.

[0070] Narrow number SPAN (0.8 or lower) num ) and ratio patterns ≥0.60 num / model vol The combination strongly indicates that the catalyst components have a narrow particle size distribution and the amount of fine particles is extremely small.

[0071] The number median particle size D50 of the catalyst component of the present invention numThe D50 ranges from 5 to <200 μm, more preferably from 8 to <150 μm. In some embodiments, D50... num Preferably in the range of 10 to <100 μm.

[0072] In a preferred embodiment, in addition to the defined SPAN num In addition, the volume SPAN of the catalyst component of the present invention vol The value is 1.10 or lower. Preferably, SPAN... vol 1.0 or lower.

[0073] Furthermore, the surface area of ​​the catalyst particles is preferably less than 20 m². 2 / g, more preferably less than 10m 2 / g.

[0074] Compounds of Group 2 metals are preferably magnesium compounds.

[0075] The transition metal compounds of groups 4 to 10, or lanthanides or actinides, are preferably compounds of groups 4 to 6, more preferably group 4 transition metal compounds or vanadium compounds, and still more preferably titanium compounds. Particularly preferred is the titanium compound of formula X. y Ti(OR 8 ) 4-y Halogenated titanium compounds, wherein R 8 It is C 1-20 Alkyl, preferably C 2-10 And more preferably C 2-8 The alkyl group, X is a halogen, preferably chlorine, and y is 1, 2, 3 or 4, preferably 3 or 4 and more preferably 4.

[0076] Suitable titanium compounds include titanium trialkoxymonochloride, titanium dialkoxydichloride, titanium trialkoxychloride, and titanium tetrachloride, with titanium tetrachloride being the most preferred.

[0077] The internal electron donor in the catalyst component of the present invention is particularly suitable as a diester of a carboxylic acid, such as a phthalate or a non-phthalic acid diester of a carboxylic acid, an ether, a diether, or an oxygen- or nitrogen-containing silicon compound, or a mixture thereof. In this application, the terms internal donor, internal electron donor, and donor have the same meaning.

[0078] The internal donor used is preferably selected from non-phthalic acid carboxylic acid (DI) esters, 1,3-diethers, their derivatives, and mixtures. More preferably, the internal electron donor is a non-phthalic acid (DI) carboxylic acid (DI) ester, particularly esters belonging to the group comprising substituted or unsubstituted malonic acid esters, maleic acid esters, succinic acid esters, substituted maleic acid esters, such as citrate, glutarate, cyclohexene-1,2-dicarboxylic acid esters, and benzoate esters, and any derivatives and / or mixtures thereof. Particularly preferred examples are, for instance, substituted maleic acid esters, more preferably citrate, especially di-2-ethylhexyl citrate.

[0079] Typically, in the catalyst composition, the amount of Ti is in the range of 1-6 wt%, the amount of Mg is in the range of 10-20 wt%, and the amount of internal donors is in the range of 10-40 wt%.

[0080] Ziegler-Natta catalyst components may optionally contain AlR 3-m-n R' m X n An alkylaluminum compound, wherein R is an alkyl group, R' is an alkoxy group of 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, X is a halogen, preferably chlorine, and m is 0, 1 or 2 and n is 0, 1 or 2, provided that the sum of m and n is at most 2.

[0081] In addition to the solid catalyst components as defined above, the catalyst of the present invention also includes a co-catalyst (also referred to as an activator) and an optional external electron donor.

[0082] The cocatalyst is preferably an organometallic compound of a Group 13 metal, typically an aluminum compound. These compounds include alkylaluminum and alkylaluminum halides. Preferably, the alkyl group is a C1-C8 alkyl group, more preferably a C1-C4 alkyl group, and the halide is a chloride. Preferably, the cocatalyst (Co) is tri(C1-C4)alkylaluminum, di(C1-C4)alkylaluminum chloride, or (C1-C4)alkyldialuminum chloride, or a mixture thereof. Most preferably, the alkyl group is ethyl. In one specific embodiment, the cocatalyst (Co) is triethylaluminum (TEAL).

[0083] External electron donors are typically used in propylene polymerization, but are also known to be used in ethylene polymerization. In this application, the terms external electron donor and external donor have the same meaning.

[0084] Suitable external electron donors (EDs) include certain silanes, ethers, esters, amines, ketones, heterocyclic compounds, and blends thereof. Silanes selected from those of general formula (A) are particularly preferred.

[0085] R a p Rb q Si(OR c ) (4-p-q) (A)

[0086] Where R a R b and R c Independently, they are identical or different straight-chain, branched, or cyclic hydrocarbon groups having 1 to 12 carbon atoms, particularly alkyl or cycloalkyl groups, wherein p and q are numbers in the range of 0 to 3, and wherein their sum p+q is equal to or less than 3; or

[0087] Silanes of general formula (B)

[0088] Si(OCH2CH3)3(NR 3 R 4 (B)

[0089] Where R 3 and R 4 These can be the same or different and represent straight-chain, branched, or cyclic hydrocarbon groups having 1 to 12 carbon atoms. Preferably, R 3 and R 4 The group is independently selected from the group consisting of: methyl, ethyl, n-propyl, n-butyl, octyl, decyl, isopropyl, isobutyl, isopentyl, tert-butyl, tert-pentyl, neopentyl, cyclopentyl, cyclohexyl, methylcyclopentyl, and cycloheptyl, and more preferably ethyl.

[0090] Most preferably, the external donor is selected from silanes of formula (A), and especially from (tert-butyl)2Si(OCH3)2, (cyclohexyl)(methyl)Si(OCH3)2, (cyclopentyl)2Si(OCH3)2 and (phenyl)2Si(OCH3)2.

[0091] The catalyst of this invention is used for the polymerization of C2 to C3. 10 Olefins, preferably C2 to C6 olefins, are optionally produced together with one or more comonomers. The most commonly produced olefin polymers are polyethylene, polypropylene, and their copolymers. The catalyst of this invention is particularly suitable for the production of polypropylene and its copolymers. Commonly used comonomers are α-olefin comonomers, preferably selected from C2-C6. 20 -α-olefin, more preferably selected from C2-C 12 -α-olefins, such as ethylene, 1-butene, isobutene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, and 1-decene, as well as dienes, such as butadiene, 1,7-octadiene, and 1,4-hexadiene, or cycloolefins, such as norbornene, and any mixture thereof. Most preferably, the comonomer is ethylene, 1-butene, and / or 1-hexene.

[0092] Catalyst preparation

[0093] The solid particle form of the catalyst component of the present invention can be prepared by any method for producing the catalyst component having the properties as defined above. Therefore, the median particle size (D50) of the resulting catalyst component... vol The range should be between 5 and 200 μm, and the quantity should be SPAN (SPAN num The ratio of the number pattern to the volume pattern is 0.80 or lower (pattern). num / model vol The value is 0.60 or higher, and the mode is... num <mode vol .

[0094] Furthermore, the catalyst component can be obtained directly, preferably directly, after being recovered from the preparation method, without the step of removing unwanted catalyst particles. Therefore, no additional particle removal step, i.e., a screening step, is required to obtain the catalyst component as defined above.

[0095] Therefore, according to a preferred embodiment of the present invention, the median granularity (D50) vol The Ziegler-Natta catalyst component, in the form of solid particles of 5 to 200 μm, is prepared by a method comprising the following steps:

[0096] a) A solution containing at least one Group 2 metal alkoxy compound, preferably at least one magnesium alkoxy compound.

[0097] b) A solution of at least one compound of a transition metal from Groups 4 to 10, or a lanthanide or actinide, preferably a transition metal from Groups 4 to 6.

[0098] c) Add the solution from step a) to the solution from step b), and

[0099] d) Recover solid catalyst component particles,

[0100] The internal electron donor or its precursor is added at any step prior to recovery step d), provided that at least a portion of the total amount of the internal electron donor or its precursor is added in step b), during step c), or after completion of step c), and wherein the amount of the catalyst component in solid particle form, SPAN, is 0.80 or lower and the ratio of the number mode to the volume mode (mode) is... num / model vol The value is 0.60 or higher, and the mode is... num <mode vol .

[0101] In addition, the catalyst components are obtained directly after the recovery step, without any need to screen out unwanted catalyst particles from the catalyst components.

[0102] Therefore, an internal electron donor (ID) or its precursor is added to a solution of at least one group 2 metal alkoxy compound (step a)), to a solution of at least one compound of group 4 to 6 transition metals (step b)), during or after step c), but before step d), provided that the full amount of the internal donor is not added to the solution of at least one group 2 metal alkoxy compound (step a)).

[0103] According to one embodiment, the addition of the donor can be performed separately between steps a) to c) (including the completion of step c). In a preferred embodiment, a first portion of the internal donor is added to the solution in step a) and a second portion is added to the solution in step b) or during or after step c). The donor can be added as is or as a solution containing a hydrocarbon solvent.

[0104] The ratio (by weight %) (first part of the donor): (second part of the donor) is 5 to 95:95 to 5, preferably 10 to 90:90 to 10, more preferably 20 to 80:80 to 20. Still more preferably, the ratio % is 10 to 50:90 to 50, especially 20 to 40:80 to 60, for example 20 to 30:80 to 70, for example 25:75.

[0105] Catalyst components in solid particle form, with a D50, can be obtained, preferably, without any screening steps. vol The range is 5 to 200 μm, the number SPAN is 0.80 or lower, and the ratio of number patterns to volumetric patterns (patterns) is... num / model vol The value is 0.60 or higher.

[0106] According to the above procedure, depending on the physical conditions, especially the temperatures used in steps c) and d), solid catalysts can be obtained via precipitation or via emulsion-curing. Emulsions are also known as liquid / liquid two-phase systems.

[0107] In both methods (precipitation or emulsion-curing), the catalyst chemistry is the same.

[0108] In the precipitation method, the solution of step a) is combined with at least one transition metal compound of step b) (step c), and the entire reaction mixture is maintained at a temperature of at least 50°C, more preferably in the temperature range of 55 to 110°C, and even more preferably in the temperature range of 70 to 100°C, to ensure complete precipitation of the catalyst component in the form of solid particles (step d).

[0109] In the emulsion-curing method, in step c), the solution from step a) is added to at least one transition metal compound from step b) at a relatively low temperature, such as -10 to below 50°C, preferably in the range of -5 to 30°C. During emulsion stirring, the temperature is typically maintained at -10 to below 40°C, preferably -5 to 30°C. Droplets of the dispersed phase of the emulsion form an active catalyst composition. The droplets are suitably cured (step d) by heating the emulsion to a temperature of 70 to 150°C, preferably 80 to 110°C.

[0110] In the emulsion-curing method, the dispersed phase of the emulsion in the form of droplets forms a catalyst portion, which is converted into solid catalyst particles during the curing step.

[0111] Catalysts prepared by the emulsion-curing method are preferably used in this invention.

[0112] In emulsion-curing methods, the formation of a liquid-liquid two-phase system (emulsion) can be promoted by adding (additional) solvents and additives such as surfactants. Surfactants act as emulsifiers, promoting emulsion formation and / or stabilizing the emulsion in a manner known in the art. Preferably, the surfactant used in this invention is an acrylic or methacrylic polymer. Particularly preferred surfactants are unbranched C... 12 To C 20 (Meth)acrylates, such as poly(hexadecyl)-methacrylate and poly(octadecyl)-methacrylate and mixtures thereof. The surfactant can be added at any step prior to step d), i.e., in steps a), b), or c). In a preferred embodiment, the surfactant is added to the solution of step a). Alternatively, the surfactant is added during or after adding the solution of step a) to the solution of step b). According to another preferred embodiment, in the case of separate donor addition, the surfactant is added before feeding the second portion of the donor into the reactor.

[0113] Surfactants can also be used in the preparation of catalyst components by the above precipitation method.

[0114] Solid particulate products produced by precipitation or emulsion-solidification methods can be washed at least once, preferably at least three times, and most preferably at least five times, with aromatic hydrocarbons and / or aliphatic hydrocarbons, preferably with toluene, heptane, or pentane and / or with TiCl4. The washing solution may also contain one or more internal donors and / or Group 13 compounds, such as trialkylaluminum, haloalkylaluminum compounds, or alkoxyaluminum compounds. Aluminum compounds may also be added during catalyst synthesis in steps a) through d). The catalyst can be further dried, for example, by evaporation or purging with nitrogen prior to final recovery in step d). If desired, the catalyst components can be slurried into an oily liquid without any drying step.

[0115] The resulting Ziegler-Natta catalyst component of the present invention is ideally in the form of spherical particles with a median volumetric particle size (D50). vol The particle size ranges from 5 to 200 μm and has a narrow particle size distribution, characterized by a number of SPAN particles. num The value is 0.80 or lower, and the ratio of the quantity pattern to the volume pattern (pattern) is... num / model vol The value is 0.60 or higher.

[0116] The surface area of ​​the catalyst particles prepared by the method described above is preferably less than 20 m². 2 / g, more preferably less than 10m 2 / g.

[0117] Typically, in the catalyst composition, the amount of Ti is 1-6 wt%, the amount of Mg is 10 to 20 wt%, and the amount of internal donors is 10 to 40 wt%.

[0118] In a more preferred embodiment, the solid catalyst component of the present invention in the form of solid particles can be obtained, more preferably, through the following procedure, wherein the solid particles have a volume median particle size (D50). vol The size ranges from 5 to 200 μm, and the SPAN thickness is [missing information]. num It is 0.80 or lower, and the ratio of the quantity pattern to the volume pattern (pattern) num / model vol ) is 0.60 or higher:

[0119] a) Provide solutions for the following items

[0120] a1) at least a group 2 metal alkoxy compound (Ax), which is the product of the reaction of a group 2 metal compound with an alcohol (A) optionally in an organic liquid reaction medium, the alcohol (A) comprising at least one ether moiety in addition to the hydroxyl moiety;

[0121] or

[0122] a2) at least a Group 2 metal alkoxide compound (Ax′), which is a reaction product of a Group 2 metal compound with an alcohol mixture of alcohol (A) and a monohydric alcohol (B) of formula ROH, optionally in an organic liquid reaction medium; or

[0123] a3) a mixture of a Group 2 metal alkoxide compound (Ax) and a Group 2 metal alkoxide compound (Bx), the Group 2 metal alkoxide compound (Bx) being a reaction product of a Group 2 metal compound with a monohydric alcohol (B), optionally in an organic liquid reaction medium; or

[0124] a4) a Group 2 metal alkoxide compound of formula M(OR1) n (OR2) m X 2-n-m , or a mixture of Group 2 metal alkoxide compounds M(OR1) n’ X 2-n’ and M(OR2) m’ X 2-m’ , wherein M is a Group 2 metal, X is a halogen, R1 and R2 are different alkyl groups having 2 to C 16 carbon atoms, and 0≤n<2, 0≤m<2 and n+m≤2, with the proviso that both n and m are not zero at the same time, 0<n'≤2 and 0<m'≤2; and

[0125] b) providing a solution of at least one transition metal of Groups 4 to 6, preferably TiCl4,

[0126] c) adding the solution from step a) to the solution of step b), and

[0127] d) recovering solid catalyst component particles,

[0128] wherein an internal electron donor or a precursor thereof is added at any step before the recovery step d), with the proviso that at least a portion of the total amount of the internal electron donor or the precursor thereof is added in step b), during step c) or after completing step c).

[0129] Suitable internal electron donors particularly suitable for use in the preparation of the catalyst component of the present invention are (di)esters of carboxylic (di)acids, such as phthalates or (di)esters of non-phthalate carboxylic (di)acids, ethers, diethers or oxygen- or nitrogen-containing silicon compounds, or precursors or mixtures thereof.

[0130] The internal donors used are preferably selected from non-phthalic acid carboxylic acid (DI) esters, 1,3-diethers, their derivatives, and mixtures. More preferred donors are non-phthalic acid (DI) carboxylic acid (DI) esters, particularly those belonging to the group comprising substituted or unsubstituted malonic acid esters, maleic acid esters, succinic acid esters, substituted maleic acid esters, such as citrate, glutarate, cyclohexene-1,2-dicarboxylic acid esters, and benzoate esters, and any derivatives and / or mixtures thereof. Particularly preferred examples are, for instance, substituted maleic acid esters, more preferably citrate, especially di-2-ethylhexyl citrate. According to this preferred embodiment, phthalic acid compounds are not used in the preparation of the solid catalyst component of the present invention.

[0131] Magnesium is the preferred metal in Group 2.

[0132] The alkoxymagnesium compounds (Ax), (Ax') and (Bx) can be prepared in situ in the first step (step a) of the catalyst preparation process by reacting a magnesium compound with one or more alcohols as described above, or the alkoxymagnesium compounds can be various alkoxymagnesium compounds prepared separately, or they can even be commercially available as ready-made alkoxymagnesium compounds (a4) and used as is in the catalyst preparation method of the present invention.

[0133] In a preferred embodiment, in step a), a solution of a2) or a3) is used, i.e., a solution of (Ax') or a mixture of (Ax) and (Bx).

[0134] An exemplary example of alcohol (A) is a glycol monoether. Preferred alcohols (A) are C2 to C4 glycol monoethers, wherein the ether moiety comprises 2 to 18 carbon atoms, preferably 4 to 12 carbon atoms. Preferred examples are 2-(2-ethylhexyloxy)ethanol, 2-butoxyethanol, 2-hexyloxyethanol, and 1,3-propanediol-monobutyl ether, 3-butoxy-2-propanol, wherein 2-(2-ethylhexyloxy)ethanol, 1,3-propanediol-monobutyl ether, and 3-butoxy-2-propanol are particularly preferred. An exemplary monohydric alcohol (B) has the formula ROH, wherein R is a straight-chain or branched C2-C... 16 Alkyl groups, preferably C4 to C5 10 More preferably, it contains C6 to C8 alkyl groups. The most preferred monohydric alcohol is 2-ethyl-1-hexanol or octanol.

[0135] Preferably, a mixture of alkoxy Mg compounds (Ax) and (Bx) or a mixture of alcohols (A) and (B) is used, and the molar ratio of Bx:Ax or B:A is 10:1 to 1:10, more preferably 6:1 to 1:6, still more preferably 5:1 to 1:3, and most preferably 5:1 to 3:1.

[0136] Alkoxymagnesium compounds can be the reaction products of alcohols as defined above with magnesium compounds selected from dialkylmagnesium, alkylalkoxymagnesium, dialkoxymagnesium, alkoxymagnesium halides, and alkylhalides. Alternatively, dialkoxymagnesium, diaryloxymagnesium, aryloxymagnesium halides, aryloxymagnesium, and alkylaryloxymagnesium can be used. The alkyl group can be similar or different C1-C. 20 Alkyl, preferably C2-C 10 Alkyl groups. Typical alkyl-alkoxy magnesium compounds used are ethylbutoxy magnesium, butylpentoxy magnesium, octylbutoxy magnesium, and octyloctoxy magnesium. Preferably, dialkyl magnesium is used. Most preferably, butyloctyl magnesium or butylethyl magnesium.

[0137] In addition to alcohols (A) and (B), magnesium compounds can also react with formula R(OH). m The alkoxymagnesium compound is obtained by reacting a polyol (C) with the polyol. If used, the preferred polyol is an alcohol in which R” is a straight-chain, cyclic, or branched C2 to C3 group. 10 Hydrocarbon groups, and m is an integer from 2 to 6.

[0138] Therefore, the alkoxymagnesium compound in step a) is selected from the group consisting of magnesium dialkoxy, magnesium diaryloxy, magnesium alkoxyhalides, magnesium aryloxyhalides, magnesium alkylalkoxy, magnesium arylalkoxy, and magnesium alkylaryloxy. Alternatively, a mixture of magnesium dihalides and magnesium dialkoxy can be used.

[0139] The solvent used to prepare the catalyst of the present invention can be selected from aromatic and aliphatic straight-chain, branched, and cyclic hydrocarbons having 5 to 20 carbon atoms, more preferably 5 to 12 carbon atoms, or mixtures thereof. Suitable solvents include benzene, toluene, cumene, xylene, pentane, hexane, heptane, octane, and nonane. Heptane and pentane are particularly preferred.

[0140] The reaction for preparing alkoxymagnesium compounds can be carried out at temperatures ranging from 0°C to 80°C, preferably from 20°C to 70°C. The most suitable temperature is selected depending on the Mg compound and one or more alcohols used.

[0141] The transition metal compounds are preferably compounds of group 4 to 6 metals, more preferably titanium compounds, and most preferably titanium halides, especially TiCl4.

[0142] Preferred implementation scheme

[0143] The invention is described in more detail below with reference to preferred embodiments. Preferred embodiments are also described in the dependent claims of the following specification. As indicated above, the ratio mode... num / model volThe value is ≥0.60, preferably ≥0.70, more preferably ≥0.80, still more preferably 0.85 or higher, and wherein the mode num <mode vol Therefore, the ratio pattern num / model vol Within the range of 0.60 to <1.0. Preferably, the ratio mode. num / model vol The value is in the range of 0.7 to <1.0, more preferably 0.80 to <1.0, and still more preferably in the range of 0.85 to <1.0.

[0144] As noted above, SPAN num Preferably 0.70 or lower, more preferably 0.60 or lower, and even 0.50 or lower. Therefore, in a particularly preferred embodiment, SPAN... num Even 0.5 or lower.

[0145] As noted, narrow quantity SPAN (SPAN) num ) and high ratio patterns num / model vol The combination strongly suggests that the amount of fine particles in the catalyst composition is extremely small.

[0146] In a preferred embodiment, SPAN num 0.70 or lower and ratio mode num / model vol It is 0.70 or higher. In a more preferred embodiment, SPAN num 0.70 or lower and ratio mode num / model vol The value is 0.80 or higher, preferably 0.85 or higher. In a still more preferred embodiment, SPAN... num 0.60 or lower and ratio mode num / model vol The value is 0.70 or higher, preferably 0.8 or higher, and even 0.85 and higher. In a particularly preferred embodiment, SPAN... num The value is 0.60 or lower, more preferably below 0.50, and the mode num / model vol It is 0.80 or higher, or even more preferably 0.85 or higher.

[0147] The median particle size D50 of the catalyst component of the present invention vol Preferably, the D50 is in the range of 8 to 200 μm, more preferably in the range of 10 to 150 μm. In some embodiments, D50 vol Preferably in the range of 20 to 100 μm.

[0148] The number median particle size D50 of the catalyst component of the present invention num Within the range of 5 to <200 μm, preferably within the range of 8 to <150 μm. In some embodiments, D50 num Preferably in the range of 10 to <100 μm.

[0149] Preferably, D50 vol and D50 num The value ranges are close to each other. However, typically, D50... num Below D50 vol Therefore, D50 is preferred. vol Within the range of 8 to 200 μm and D50 num More preferably, D50 is preferred in the range of 5 to <200 μm. vol Within the range of 10 to 150 μm and D50 num Within the range of 8 to <150 μm. Particularly preferred is D50. vol Within the range of 20 to 100 μm, and D50 num Within the range of 10 to <100 μm.

[0150] In a particularly preferred embodiment, D50 vol SPAN has a range of 8 to 200 μm. num For values ​​below 0.80 and in ratio mode num / model vol It is 0.70 or higher. Additionally, the D50... num Within the range of 5 to <200 μm. According to a preferred embodiment, D50 vol Within the range of 8 to 200 μm, more preferably within the range of 10 to 150 μm and SPAN num 0.70 or lower, preferably 0.60 or lower, and ratio mode num / model vol The value is 0.7 or higher, preferably 0.8 or higher.

[0151] According to what is still a preferred embodiment, D50 vol Within the range of 8 to 200 μm, more preferably within the range of 10 to 150 μm and SPAN num The value is 0.60 or lower, more preferably below 0.50, and the mode num / model vol It is 0.8 or higher, more preferably 0.85 or higher.

[0152] In addition to the characteristics of solid catalyst particles as mentioned above, volume SPAN volIt is 1.1 or lower. Preferably, SPAN vol 1.0 or lower.

[0153] The catalyst component of the present invention has a uniform particle size distribution and the particles preferably have a low surface area, which is less than 20 m². 2 / g, preferably less than 10m 2 / g. Furthermore, in a preferred embodiment, the catalyst particles are characterized by a uniform distribution of catalytically active sites throughout the entire catalyst particle.

[0154] In the catalyst composition of the present invention, the Group 2 metal is preferably magnesium.

[0155] Transition metal compounds from groups 4 to 6 are more preferably titanium compounds, and most preferably titanium tetrachloride.

[0156] The internal electron donor used is preferably selected from diesters of non-phthalic acid carboxylic acids, 1,3-diethers, their derivatives, and mixtures. Particularly preferred internal electron donors are diesters of non-phthalic acid carboxylic acids, especially those belonging to the group comprising substituted or unsubstituted malonic esters, maleic esters, succinates, substituted maleic esters, such as citrate, glutarate, cyclohexene-1,2-dicarboxylic acid esters, and benzoates, and any derivatives and / or mixtures thereof. More preferred examples of the donor are substituted maleic esters, most preferably citrate, especially di-2-ethylhexyl citrate.

[0157] According to a preferred embodiment, the catalyst component of the present invention is in the form of solid spherical particles and does not contain any external support material, such as silica or any other prepared MgCl2-based support. More preferably, the catalyst component is prepared by the method described above. According to the preferred preparation method, a solution of at least one Group 2 metal alkoxy compound (preferably at least one alkoxy magnesium) and at least one compound of Group 4-6 transition metals (most preferably TiCl4) is contacted with an internal electron donor and reacted in solution, followed by precipitation or emulsion-curing to form solid catalyst particles. The final catalyst contains the internal electron donor as defined above, and the amounts of Ti and Mg indicated above. The preferred method produces a catalyst component in solid particle form having the characteristics indicated above. Furthermore, the solid catalyst particles are characterized by a uniform distribution of catalytic active sites throughout the catalyst particles.

[0158] Solid particles are obtained without any need to remove unwanted catalyst particles. Therefore, without using any particle sorting steps, such as sieving, to remove unwanted catalyst particles, a particle with a D50 as defined above is obtained. vol SPAN numSum and ratio patterns num / model vol The final Ziegler-Natta catalyst component is in solid particle form.

[0159] polymerization

[0160] The catalyst of this invention can be used in any commonly used single-mode and multi-mode methods for the production of polyolefins. Polymerization can be carried out in a slurry, solution, or gas-phase reactor, or a combination thereof. Typically, ethylene and propylene (co)polymers are produced on a commercial scale in a multi-mode process configuration. Such multi-mode polymerization methods known in the art comprise at least two polymerization stages. It is preferable to operate multiple polymerization stages in a cascaded manner. Suitable methods comprising cascaded slurry stages and gas-phase polymerization stages are disclosed in particular in WO92 / 12182, WO96 / 18662, and WO98 / 58975.

[0161] In a multi-mode polymerization configuration, the polymerization stage includes a polymerization reactor selected from slurry reactors and gas-phase reactors. In a preferred embodiment, the multi-mode polymerization configuration includes at least one slurry reactor, followed by at least one gas-phase reactor.

[0162] The catalyst can be transferred to the polymerization process using any method known in the art. Thus, the catalyst can be suspended in a diluent and kept as a homogeneous slurry. Particularly preferred is the use of an oil with a viscosity of 20 to 1500 mPa·s as a diluent, as disclosed in WO-A-2006 / 063771. Alternatively, the catalyst can be mixed with a viscous mixture of grease and oil, and the resulting paste can be fed into the polymerization zone. Furthermore, the catalyst can be precipitated, and a portion of the resulting catalyst sludge can be introduced into the polymerization zone, for example, in a manner disclosed in EP-A-428054.

[0163] Polymerization in the slurry can be carried out in an inert diluent, typically a hydrocarbon diluent such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or mixtures thereof. Preferably, the diluent is a low-boiling-point hydrocarbon having 1 to 4 carbon atoms, such as propane or a mixture of such hydrocarbons. In propylene polymerization, propylene monomer is typically used as the reaction medium.

[0164] The temperature during slurry polymerization is typically 40 to 115°C, preferably 60 to 110°C, and particularly 70 to 100°C, for example 70 to 90°C. The pressure is 1 to 150 bar, preferably 10 to 100 bar.

[0165] Slurry polymerization can be carried out in any known reactor used for slurry polymerization. Such reactors include continuous stirred tank reactors and loop reactors. Polymerization is particularly preferred in a loop reactor. As is known in the art, hydrogen is optionally fed into the reactor to control the molecular weight of the polymer. In addition, one or more α-olefin comonomers can be added to the reactor. The actual amounts of such hydrogen and comonomer feed depend on the desired melt index (or molecular weight), density, or comonomer content of the resulting polymer.

[0166] Polymerization in the gas phase can be carried out in a fluidized bed reactor, a fast fluidized bed reactor, a settling bed reactor, or any combination thereof.

[0167] Typically, fluidized bed or settling bed polymerization reactors are operated at temperatures ranging from 50 to 100°C, preferably 65 to 90°C. The pressure is suitably 10 to 40 bar, preferably 15 to 30 bar.

[0168] If necessary, an antistatic agent can also be introduced into the slurry and / or gas-phase reactor. The method may further include a pre-reactor and a post-reactor.

[0169] A prepolymerization step may precede the actual polymerization step. The prepolymerization step can be carried out in a slurry or in the gas phase. Preferably, prepolymerization is carried out in a slurry, and particularly in a loop reactor. The temperature in the prepolymerization step is typically 0 to 90°C, preferably 20 to 80°C, and more preferably 30 to 70°C.

[0170] Pressure is not critical and is typically between 1 and 150 bar, preferably between 10 and 100 bar.

[0171] Polymerization can be carried out continuously or in batches, preferably continuously on an industrial scale.

[0172] Experimental Section

[0173] Measurement methods

[0174] Ti, Mg and Al content – ​​ICP-OES

[0175] The sample, consisting of dry catalyst powder, is mixed to obtain a representative test portion. Approximately 20-50 mg of the sample is taken into a 20 ml crimp cap vial under an inert atmosphere, and the precise weight of the powder is recorded.

[0176] Prepare a known volume (V) of test solution in a volumetric flask. In the cooled vial, digest the sample by adding a small amount of freshly distilled (D) water (5% of V), followed by concentrated nitric acid (HNO3, 65%, 5% of V). Transfer the mixture to a volumetric flask. Dilute the solution with D water to a final volume V and allow it to stabilize for two hours.

[0177] Elemental analysis of aqueous samples was performed at room temperature using a Thermo Elemental iCAP 6300 inductively coupled plasma-emission spectrometer (ICP-OES). The instrument was calibrated for Al, Ti, and Mg using a blank (5% HNO3 solution) and six standards (0.5 ppm, 1 ppm, 10 ppm, 50 ppm, 100 ppm, and 300 ppm of 5% HNO3 DI aqueous solution for Al, Ti, and Mg). Linear fitting and 1 / concentration weighting were used for the calibration curves.

[0178] Before proceeding with the analysis, validate and adjust the calibration using a blank and 300 ppm Al, 100 ppm Ti, and Mg standards (instrument function called "reslope"). Run the quality control sample (QC; 20 ppm Al and Ti, 50 ppm Mg, in 5% HNO3 D aqueous solution) to confirm the reset slope. Run the QC sample after every 5th sample and at the end of the planned analytical set.

[0179] Magnesium content was monitored using a 285.213 nm line, and titanium content was monitored using a 336.121 nm line. Aluminum content was monitored via a 167.079 nm line when the Al concentration in the test section was 0-10 wt%, and via a 396.152 nm line for Al concentrations above 10 wt%.

[0180] The reported value is the average of three consecutive aliquots of the same sample, and is in turn correlated with the original catalyst sample by inputting the original mass and dilution volume of the test portion into the software.

[0181] Internal electron donor content - GC-FID

[0182] The sample, consisting of dry catalyst powder, is mixed to obtain a representative test portion. Approximately 60-90 mg of the sample is taken into a 20 ml capped vial under an inert atmosphere, and the precise weight of the powder is recorded.

[0183] The test solution, consisting of an internal donor in dichloromethane, was prepared by liquid-liquid extraction of the sample, water, and organic solvent as follows: The test fraction was dissolved in 5 ml of dichloromethane. Using a precision microsyringe, a solution consisting of dimethyl pimecrolate (0.28 V / V-%) and deionized water was added in 1 ml volume. The suspension was sonicated for 20 min, and the phases were allowed to settle for separation. The organic phase was sampled and filtered into an instrument vial using a 0.45 μm filter.

[0184] The measurements were performed on an Agilent 7890B gas chromatograph equipped with a flame ionization detector. A ZB-5HT Inferno column (15m x 320μm x 0.25μm) was used, with midpoint backflush via a three-channel auxiliary EPC and a 1.5m x 320μm x 0μm pre-column confinement capillary. The oven was maintained at an initial temperature of 40°C for 3 min. The ramp program consisted of a first ramp rate of 5°C / min to 70°C, a second ramp rate of 40°C / min to 330°C, and a third ramp rate of 20°C / min to 350°C with a hold time of 1 min.

[0185] The inlet was operated in split mode. The injection volume was 1 μL, the inlet temperature was 280 °C, the pressure was 2.941 psi, the total flow rate was 19.8 mL / min, and the split ratio was 20:1. The carrier gas was 99.995% He, with a pre-column flow rate of 0.8 mL / min and an additional flow rate of 1 mL / min from the backflushing EPC to the analytical column. The FID detector was operated at 370 °C, with an N2 makeup flow rate of 25 mL / min, a synthesis air flow rate of 350 mL / min, and a hydrogen flow rate of 35 mL / min.

[0186] The FID signal from the chromatogram was integrated and calculated for a series of standardized samples using the response ratio between the signals of the internal donor and the internal standard dimethyl pimecrolate. Identity was determined by retention time. Standardization of the internal donor was performed using four standardized solutions of a series of known masses of internal donors, corresponding to 7.68 mg to 19.11 mg of a 100 mg sample treated with the same sample formulation as the sample. The calibration curve for the response ratio was linear without sample concentration weighting. Standardization was validated using quality control samples for each run. All test solutions were run in duplicate. The mass of the test portion was used to calculate the internal electron donor content of the two replicates, and the results were reported as an average.

[0187] Granularity Distribution – Automated Image Analysis

[0188] A sample consisting of dry catalyst powder is mixed to obtain a representative test fraction. Approximately 50 mg of the sample is taken into a 20 ml capped vial under an inert atmosphere, and the precise weight of the powder is recorded. A test solution is prepared by adding white mineral oil to the powder to maintain a concentration of approximately 0.5–0.7% by weight. The test solution is carefully mixed before obtaining a fraction, which is then placed in a measuring cell suitable for the instrument. The measuring cell should be positioned such that the distance between the two optically clean glass plates is at least 200 μm.

[0189] Image analysis was performed at room temperature on a Malvern Morphologi 3G system. The measurement cell was placed on a microscope platform that moved with high precision in all directions. Physical dimensions within the system were measured relative to an internal grating or normalized using an external calibration plate. A region of the measurement cell was selected to ensure the particle distribution was representative of the test solution. This region was recorded as a partially overlapping image using a CCD camera, and the image was stored in system-specific software via an objective lens with sufficient working distance and a microscope with 5x magnification. A transmission light source was used and the illumination intensity was adjusted before each run. All images were recorded using a set of four focal planes over the selected region. The collected images were analyzed using software where particles were individually identified by comparison with the background using predefined grayscale settings for the material. A classification scheme was applied to the individually identified particles, allowing the collected particle swarms to be identified as belonging to the physical sample. Based on the selection of the classification scheme, other parameters could be attributed to the sample.

[0190] The particle diameter is calculated as the circular equivalent (CE) diameter. The particle size range included in the distribution is 6.8–200 μm. The distribution is calculated as a quantity moment-ratio density function distribution, and a statistical descriptor is calculated based on this quantity distribution. The quantity distribution can be recalculated for each bin size to estimate the volumetric transformation distribution.

[0191] All graphical representations are based on a smoothing function with 11 points, and the statistical descriptors of the groups are based on unsmoothed curves. The pattern is manually determined as the peak of the smoothed frequency curve. The span is calculated as (CE D[x,0.9]-CE D[x,0.1]) / CE D[x,0.5].

[0192] The following particle size and particle size distribution indices were used in the experiment:

[0193] D90 vol = The volumetric value of the particle diameter at 90% of the cumulative size.

[0194] D10 vol = Volumetric value of particle diameter at 10% cumulative size

[0195] D50 vol = Volume of particle diameter at 50% cumulative size (median particle size, vol)

[0196] SPAN vol =(D90) vol –D10 vol ) / D50 vol

[0197] D90 num = The number of particles at 90% cumulative size

[0198] D10 num = The number of particles at 10% cumulative size,

[0199] D50 num = The number of particles at 50% cumulative size (median particle size, number)

[0200] SPAN num =(D90) num –D10 num ) / D50 num

[0201] Volume mode vol and quantity pattern num Granularity refers to the granularity most commonly seen in a distribution (in terms of volume or quantity, respectively).

[0202] melt flow rate

[0203] MFR2: 230℃, 2.16kg load

[0204] The melt flow rate was measured in accordance with ISO 1133 and expressed as g / 10min. Example

[0205] raw material

[0206] TiCl4 (CAS 7550-45-90) is available from commercial sources.

[0207] A 20% toluene solution of butyl ethyl magnesium (Mg(Bu)(Et)) supplied by Crompton

[0208] 2-Ethylhexanol, supplied by Merck Chemicals

[0209] 3-Butoxy-2-propanol, provided by Sigma-Aldrich

[0210] Bis(2-ethylhexyl) citrate, provided by Contract Chemicals

[0211] 1-254, provided by Evonik

[0212] Heptane, supplied by Chevron

[0213] Example A: Preparation of soluble Mg-alkoxy compounds and Mg complexes

[0214] A.1. Preparation of soluble Mg-alkoxy compounds

[0215] 3.4 L of 2-ethylhexanol and 810 mL of propylene glycol butyl ether (molar ratio 4 / 1) were added to a 20 L reactor. Then, 7.8 L of a 20% toluene solution of BEM (butylethyl magnesium), supplied by Crompton GmbH, was slowly added to the well-stirred alcohol mixture. The temperature was maintained at 10 °C during the addition. After the addition, the temperature of the reaction mixture was raised to 60 °C and mixing continued at this temperature for 30 minutes. Finally, after cooling to room temperature, the obtained Mg-alkoxy compound was transferred to a storage container.

[0216] A.2. Preparation of Mg complex

[0217] 21.2 g of the Mg alkoxy compound prepared in Example A.1. was mixed with 4.0 ml of the donor (bis(2-ethylhexyl) citrate) for 5 min. Immediately after mixing, the resulting Mg complex was used in the preparation of the catalyst component.

[0218] Comparative Example 1 (CE1)

[0219] Preparation of catalyst components

[0220] Add 13.0 ml of titanium tetrachloride to a 100 ml Easy Max reactor equipped with a mechanical stirrer at 15°C. Adjust the mixing speed to 500 rpm. Maintain the temperature at 15°C, and over 20 minutes, add 16.8 g of the Mg-complex prepared in Example A.2 to TiCl4. Add 0.7 ml of... 1-254 ml of heptane and 21.0 ml of toluene were added to form an emulsion. Mixing was continued at 15°C (700 rpm) for 30 minutes, followed by raising the reactor temperature to 90°C over 45 minutes. The reaction mixture was then stirred at 700 rpm at 90°C for another 30 minutes. Stirring was then stopped, and the reaction mixture was allowed to settle at 90°C for 15 minutes. The solid material was washed five times: five times with toluene, a TiCl4 / donor mixture, toluene, heptane, and heptane, respectively, while stirring at 80°C for 20 minutes. After stopping stirring, the reaction mixture was allowed to settle for 10-30 minutes, followed by siphoning between washes.

[0221] After the final wash, the temperature was lowered to 70°C, followed by siphoning and then N2 purging for 60 minutes to obtain air-sensitive powder.

[0222] The catalyst was separated in the form of spherical particles. Catalyst analysis and morphological properties are disclosed in Table 1.

[0223] Comparative Example 2 (CE2)

[0224] Preparation of catalyst components

[0225] The catalyst components were prepared in the same manner as in CE1, except that 16.8 g of the Mgalkoxy compound from Example A.1 was added to TiCl4 and the donor was added to the mixture prior to heptane (9 ml). The catalyst was separated in the form of spherical particles. Catalyst analysis and morphological properties are disclosed in Table 1.

[0226] Embodiment 1 of the Invention (IE1)

[0227] Preparation of catalyst components

[0228] The catalyst components were prepared in the same manner as in CE2, but with the addition of Viscoplex to the Mg-alkoxy compound. The catalyst was separated in the form of spherical particles. Catalyst analysis and morphological properties are disclosed in Table 1.

[0229] Embodiment 2 of the Invention (IE2)

[0230] Preparation of catalyst components

[0231] The catalyst components were prepared in the same manner as in CE2, but 25% of the donor was added to the Mg-alkoxy compound before being added to TiCl4, and 75% of the donor was added in the same manner as in CE2.

[0232] The catalyst was separated in the form of spherical particles. Catalyst analysis and morphological properties are disclosed in Table 1.

[0233] Comparative Example 3 (CE3)

[0234] According to Example 8 of WO 2004 / 029112, a solid catalyst component was prepared in addition, except that diethylaluminum chloride was used as the aluminum compound instead of triethylaluminum.

[0235] Table 1

[0236] Ti / wt% 3.3 2.4 3.3 2.9 2.5 Mg / wt% 15.0 12.0 15.4 14.8 12.2 Donor / weight% 25.8 20.6 24.3 24.5 21.0 <![CDATA[D50 vol / μm]]> 46.8 32.1 24.3 40.2 53.3 <![CDATA[D90 vol / μm]]> 72.5 39.9 45.4 71.1 73.6 <![CDATA[D10 vol / μm]]> 22.2 20.3 19.4 31.8 29.0 <![CDATA[SPAN vol ]]> 1.07 0.61 1.07 0.98 0.84 <![CDATA[D50 num / μm]]> 16.9 22.0 21.7 35.8 22.2 <![CDATA[D90 num / μm]]> 39.1 34.1 26.8 43.9 50.8 <![CDATA[D10 num / μm]]> 9.0 13.3 17.2 26.6 10.4 <![CDATA[SPAN num ]]> 1.79 0.95 0.45 0.48 1.82 <![CDATA[Mode vol / μm]]> 52.8 35.5 24.1 41.2 60.6 <![CDATA[Mode num / μm]]> 17.8 31.2 21.2 36.6 17.4 <![CDATA[Mode num / Mode vol > 0.34 0.88 0.88 0.88 0.28

[0237] polymerization

[0238] A 5-liter stainless steel reactor was used for propylene polymerization.

[0239] Approximately 0.9 ml of triethylaluminum (TEA) (obtained from Witco and used as is) as a co-catalyst, approximately 0.13 ml of dicyclopentyldimethoxysilane (DCDS) (obtained from Wacker and dried with molecular sieves) as an external donor, and 30 ml of n-pentane were mixed and allowed to react for 5 minutes. Half of the mixture was then added to the polymerization reactor, while the other half was mixed with approximately 20 mg of catalyst. After another 5 minutes, the catalyst / TEA / donor / n-pentane mixture was added to the reactor. The Al / Ti ratio was 250 mol / mol and the Al / DCDS ratio was 10 mol / mol. 200 mmol of hydrogen and 1400 g of propylene were introduced into the reactor, and the temperature was raised to the polymerization temperature (80 °C) over approximately 20 minutes. After reaching the polymerization temperature, the polymerization time was 60 minutes, after which the formed polymer was removed from the reactor. The polymerization results are disclosed in Table 2.

[0240] The polymerization results showed that, as expected, the catalyst activity and melt flow rate remained at the same level in all the inventive embodiments and Comparative Examples 1 and 2, indicating that the catalyst of the present invention, with its excellent particle size distribution, meets the polymerization criteria. In Comparative Example 3, these values ​​differed from the other embodiments; however, the catalysts were fundamentally different from a morphological point of view, and the chemistry of the catalysts was different. As explained in the specification, reactor fouling and clogging will not be observed in small-scale polymerization tests.

[0241] Table 2

[0242]

Claims

1. A Ziegler-Natta catalyst component, wherein the Ziegler-Natta catalyst component has a median particle size D50. vol It is in the form of solid particles ranging from 5 to 200 µm and contains: i) Compounds of Group 2 metals according to the IUPAC Inorganic Chemical Nomenclature of 1989, wherein the Group 2 metal is magnesium. ii) Compounds of transition metals of groups 4 to 6 according to the IUPAC Inorganic Chemical Nomenclature 1989, wherein the compounds of transition metals of groups 4 to 6 are titanium compounds, and iii) Internal electron donor, The number of solid particles mentioned above is SPAN (SPAN num The ratio of the number pattern to the volume pattern is 0.80 or lower (pattern). num / model vol The value is 0.60 or higher, and the mode is... num <mode vol ;and The Ziegler-Natta catalyst component can be obtained directly by a method including the following steps without any particle sieving steps: a) Provide a solution of at least one alkoxymagnesium, b) Provide a solution of at least one titanium compound, c) Add the solution from step a) to the solution from step b), and d) Recover the solid particles of the Ziegler-Natta catalyst component. Wherein an internal electron donor or its precursor is added at any step prior to the recovery step d), provided that at least a portion of the total amount of the internal electron donor or its precursor is added in step b), during step c), or after the completion of step c), and wherein (i') Add a first portion of the internal electron donor to the solution of step a), and add a second portion of the internal electron donor to the solution of step b), or during or after step c), and / or (ii') Add the surfactant to the solution from step a).

2. The Ziegler-Natta catalyst component according to claim 1, wherein SPAN num It is 0.70 or lower.

3. The Ziegler-Natta catalyst component according to claim 1 or 2, wherein the mode num / model vol The ratio is 0.70 or higher.

4. The Ziegler-Natta catalyst component according to claim 1 or 2, wherein the surface area of ​​the solid particles is less than 20 m². 2 / g.

5. The Ziegler-Natta catalyst component according to claim 1, wherein the titanium compound is titanium halide.

6. The Ziegler-Natta catalyst component according to claim 5, wherein the titanium halide is TiCl4.

7. The Ziegler-Natta catalyst component according to claim 1 or 2, wherein the internal electron donor is selected from esters, 1,3-diethers, derivatives thereof, and / or mixtures of non-phthalic acid carboxylic acids.

8. The Ziegler-Natta catalyst component according to claim 7, wherein the internal electron donor is selected from esters of non-phthalic acid carboxylic acids and any derivatives and / or mixtures thereof.

9. The Ziegler-Natta catalyst component according to claim 7, wherein the internal electron donor is selected from diesters, derivatives and / or mixtures of non-phthalic acid dicarboxylic acids.

10. The Ziegler-Natta catalyst composition according to claim 1, wherein the amount of Ti in the Ziegler-Natta catalyst composition is in the range of 1 to 6 wt%, the amount of Mg is in the range of 10 to 20 wt%, and the amount of the internal electron donor is in the range of 10 to 40 wt%.

11. A method for producing a Ziegler-Natta catalyst component in solid particulate form as defined in any one of claims 1 to 10, the method comprising the steps of: a) Provide a solution of at least one alkoxymagnesium, b) Provide a solution of at least one titanium compound, c) Add the solution from step a) to the solution from step b), and d) Directly recover the solid particles of the Ziegler-Natta catalyst component without any particle screening step. Wherein an internal electron donor or its precursor is added at any step prior to the recovery step d), provided that at least a portion of the total amount of the internal electron donor or its precursor is added in step b), during step c), or after the completion of step c), and The number of the Ziegler-Natta catalyst component in solid particle form obtained directly from step d) is SPAN 0.80 or lower, and the ratio of the number mode to the volume mode (mode) is... num / model vol The value is 0.60 or higher, and the mode is... num < pattern vol ,and in, i) Adding a first portion of the internal electron donor to the solution of step a), and adding a second portion of the internal electron donor to the solution of step b), or during or after step c), and / or ii) Add the surfactant to the solution from step a).

12. The method of claim 11, wherein the titanium compound is a titanium halide.

13. The method of claim 11, wherein the Ziegler-Natta catalyst component in solid particle form is prepared by precipitation or by emulsion-curing.

14. The method according to claim 11 or 12, wherein the method comprises the following steps: a) Provide solutions for the following: a1) at least an alkoxymagnesium compound Ax, which is the product of the reaction of a magnesium compound with an alcohol (A) optionally in an organic liquid reaction medium, said alcohol (A) comprising at least one ether moiety in addition to the hydroxyl moiety; or a2) At least an alkoxymagnesium compound Ax', which is the product of the reaction of a magnesium compound with said alcohol (A) and a monohydric alcohol (B) of formula ROH, optionally in an organic liquid reaction medium, wherein R is a straight-chain or branched C2-C 16 alkyl groups; or a3) A mixture of the alkoxymagnesium compound Ax and the alkoxymagnesium compound Bx, wherein the alkoxymagnesium compound Bx is the product of the reaction of the magnesium compound and the monohydric alcohol (B) optionally in an organic liquid reaction medium; or a4)M(OR1) n (OR2) m X 2-n-m Alkoxymagnesium compounds or alkoxymagnesium compounds M(OR1) n’ X 2-n’ And M(OR2) m’ X 2-m’ A mixture of substances, wherein M is magnesium, X is a halogen, R1 and R2 are different alkyl groups having 2 to 16 carbon atoms, and 0 < n < 2, 0 < m < 2 and n+m < 2. The condition is that n and m are not both zero at the same time, and 0 < n' < 2 and 0 <m’ < 2; and b) Provide a solution of at least one titanium compound, c) Add the solution from step a) to the solution from step b), and d) Recover the solid particles of the Ziegler-Natta catalyst component. Wherein, an internal electron donor or its precursor is added at any step prior to the recovery step d), provided that at least a portion of the total amount of the internal electron donor or its precursor is added in step b), during step c), or after completion of step c); and in, i) Adding a first portion of the internal electron donor to the solution of step a), and adding a second portion of the internal electron donor to the solution of step b), or during or after step c), and / or ii) Add the surfactant to the solution from step a).

15. The method according to claim 11 or 12, wherein the internal electron donor is selected from esters, 1,3-diethers, derivatives thereof, and / or mixtures thereof of non-phthalic acid carboxylic acids.

16. The method of claim 15, wherein the internal electron donor is selected from esters of non-phthalic acid carboxylic acids and any derivatives and / or mixtures thereof.

17. The method of claim 15, wherein the internal electron donor is selected from diesters, derivatives and / or mixtures of non-phthalic acid dicarboxylic acids.

18. A Ziegler-Natta catalyst, said Ziegler-Natta catalyst comprising a Ziegler-Natta catalyst component in solid particulate form as defined in any one of claims 1 to 10 or prepared by the method defined in any one of claims 11 to 17, and Co-catalysts and optional external electron donors for compounds of Group 13 metals.

19. The Ziegler-Natta catalyst according to claim 18 for the production of C2 to C 10 Uses of α-olefin polymers or their comonomers.

20. Use of the Ziegler-Natta catalyst according to claim 18 for the production of propylene or ethylene polymers or their comonomers.

21. A polymerization method, the polymerization method comprising generating C2 to C 10 Under the polymerization conditions of α-olefin polymers, in the presence of the Ziegler-Natta catalyst component as defined in any one of claims 1 to 10 or produced according to the method defined in any one of claims 11 to 17, C2 to C 10 α-olefins are optionally polymerized together with comonomers.

22. The polymerization method according to claim 21, wherein it is carried out under polymerization conditions that produce polyethylene or polypropylene or copolymers thereof.

Citation Information

Patent Citations

  • A ziegler-Natta catalyst component

    EP0376936A2

  • Device for feeding a mud-like catalytic mixture into a polymerization reactor

    EP0428054A1

  • A procatalyst for polymerization of olefins containing a trans-esterification product of a lower alcohol and a phthalic acid ester

    EP0591224A1

  • Procatalyst for ethylene polymer production, method for its preparation and use

    EP0688794A1

  • Polymerization catalyst

    EP0810235A2